Anoxic Microbial Community Robustness Under Variation of Hydraulic Retention Time and Availability of Endogenous Electron Donors - Okada, Dagoberto Y.; Costa, Rachel B. [UNESP]; Garcia, Caroline de Cassia B.; Pozzi, Eloisa; Souza, Theo S. O.; Foresti, Eugenio (Springer, 2020)
The ADNMED (Anaerobic Digestion, Nitrification, and Mixotrophic Endogenous Denitrification) system comprises a triple chamber configuration that was shown to provide high-quality effluent regarding carbon, nitrogen, and sulfide. Hydraulic retention time (HRT) was 7 h in the anaerobic and anoxic chambers, and 5 h in the aerobic chamber (stage A). Sewage was directly added to the anoxic chamber to provide extra organic electron donors for denitrification (stage B) to improve the nitrogen removal efficiency (stage A 47 +/- 19%). The addition of sewage at a flow rate equivalent to 10% of the feed flow increased nitrogen removal efficiency to 61 +/- 12%. Illumina (R) sequencing revealed a restructuring of the microbial community in the anoxic chamber, according to the availability of the endogenous electron donors for denitrification. At stage A, denitrification was related to the decay of biomass, while the addition of sewage during stage B stimulated the establishment of fermentative bacteria.
Keywords: Domestic sewage; Endogenous electron donors; Sulfide-driven autotrophic denitrification; Nitrogen removal; Illumina sequencing